Juvenile idiopathic arthritis in two tertiary centres in the Western Cape, South Africa - Weakley, Kate (Department of Paediatrics and Child Health, 2014)
Juvenile idiopathic arthritis (JIA) is defined as arthritis of unknown aetiology that begins before the 16th birthday and persists for at least 6 weeks, other conditions being excluded. As JIA is a disease with serious functional implications, a descriptive study would not be complete without reviewing both the functional and clinical parameters of the disease. There has been very little African data on this subject. The objective of this study is to describe the functional disability and clinical disease characteristics in a sample of children diagnosed with JIA in Cape Town, South Africa.